Designing an Overtime Request Information System Using the SDLC Method at PT. Laju Omega Digital - Setiadi, Dedi; Sopian, Abu; Mubarok, Royhan Ibnu; Widyahastuti, Febrianti (Universitas Mohammad Husni Thamrin, 2025)
The development of information technology has had a significant impact on human resource management, including the process of submitting overtime requests to employees. This process is crucial to ensure optimal productivity, especially in companies with many divisions and employees. PT. Laju Omega Digital still uses manual methods for recording overtime, which causes delays in the process, difficulties in tracking data, and a lack of transparency in overtime approvals. Therefore, a web-based system is needed that can automate and improve the efficiency of managing overtime requests. This study aims to design and develop a web-based information system that allows employees to submit overtime digitally, as well as facilitates admins in managing overtime request data. This system is built using the Laravel framework with a Bootstrap-based design to be more responsive and easy to use. The main features developed include a login system, an overtime request form, overtime verification and approval, and data recapitulation for further analysis. The research methods used include observation, interviews, and literature studies. System development is carried out using the System Development Life Cycle (SDLC) model, including needs analysis, system design, implementation, testing, and evaluation. The research results show that the developed system can improve the efficiency of overtime requests, reduce recording errors, and provide greater transparency in the approval process. With this system's implementation, PT. Laju Omega Digital can improve productivity and the quality of human resource management.